Recent advances in shape memory superhydrophobic surfaces: Concepts, mechanism, classification, applications and challenges - Zhan, Yanlong; Li, Wen; Amirfazli, Alidad; Yu, Sirong (Polymer (Guilford), 2022)
Smart control of surface wettability has attracted widespread attention, especially for superhydrophobic surfaces. Based on the shape memory effect (SME) of the shape memory polymers (SMPs), shape memory superhydrophobic surfaces can intelligently control the surface topographies and wettability and have motivated great interest for extensive application prospects. Here, recent achievements and corresponding applications of shape memory superhydrophobic surfaces were reviewed. The research background, concepts and significance were firstly introduced. Following, the fundamental wetting theory and models, evaluation of SME and mechanism was revealed. Then recent advances including of magnetic, photo, electrical, thermo and chemical-induced shape memory superhydrophobic surfaces were reviewed with an advanced perspective. Subsequently, the major representative applications including wettability control, droplet manipulation, self-healing and other smart applications were summarized. Finally, the problems and perspectives on future research directions were proposed. It is wished that this review can inspire the development of shape memory superhydrophobic surfaces for its following realistic applications. Based on the shape memory effect (SME) of the shape memory polymers (SMPs), shape memory superhydrophobic surfaces can intelligently control the surface topographies and wettability and have motivated great interest for extensive application prospects. The recent advances including of magnetic, photo, electrical, thermo and chemical-induced shape memory superhydrophobic surfaces were reviewed with an advanced perspective. The major representative applications including wettability control, droplet manipulation, self-healing and other smart applications were summarized. [Display omitted]